Growth of hempedu bumi (Andrographis paniculata) as affected by inorganic and organic fertilizers - Siti Hajar Mat Zin.
Hempedu bumi (Andrographis paniculata) is one of the local medicinal herbs identified for development. Research and development work on local medicinal herbs is still limited. For most of the herbs, many aspects of growth requirement including plant nutrition and fertilization have not been fully studied. The type of fertilizer used can affect plant growth as well as the environment. An experiment was conducted at Ladang 2, UPM to study the effects of organic and inorganic fertilizers on growth performance of hempedu bumi. The treatments consist of 100% JITU (3:3:3), 100% NPK green (15:15:15), combination of 50% JITU and 50% NPK green and combination of 75% JITU and 25% NPK green. Seedlings were planted in topsoil, peat and sand mixture (3:2:1). All fertilizers were applied at a rate of 180 kg N/ha. Treatments were arranged in Completely Randomized Design (CRD) with three replications. Data were collected for analysis on the 10th week after planting. Results showed the plant growth significantly affected by organic and inorganic fertilizers. Application of 25% NPK green plus 75% JITU gave the highest total plant fresh weight, fresh weight of leaves and stem, total plant dry weight, dry weight of stem and root, plant height, total leaf area, leaf chlorophyll content and nitrogen content of leaf compared to 100% JITU fertilizer and 100% NPK green fertilizer. Application of 100% JITU fertilizer produced the lowest result compared to all other treatments.